Bridging the gap: attitudes and practices toward complementary and alternative medicine among oncology patients and healthcare professionals in Croatia - Armano, Ljerka; Vasiljev, Vanja; Rukavina, Tomislav; Juraga, Denis; Racz, Aleksandar; Tešić, Vanja (Frontiers in Psychology, 2025)
The prevalence of complementary and alternative medicine (CAM) use among oncology patients ranges from 30 to 80%, particularly higher in the United States compared to Europe. However, limited research exists on the attitudes of healthcare professionals and oncology patients toward CAM, especially within Western evidence-based medical settings. This study aims to address this gap by assessing CAM use prevalence among healthcare professionals and oncology patients and analyzing their cognitive, affective, and behavioral attitudes. Additionally, it explores the influence of sociodemographic factors and personal experiences on these attitudes. A cross-sectional survey was conducted between November 2022 and May 2023 at University Hospital Center Sisters of Mercy, Zagreb, Croatia. The study included 832 participants: 411 oncology patients and 421 healthcare professionals (100 physicians, 321 nurses/technicians). Data were collected using modified versions of the Health Belief Questionnaire (CHBQ) and Integrative Medicine Attitude Questionnaire (IMAQ). Statistical analysis included descriptive methods and tests such as Chi-square, Mann–Whitney U, Kruskal-Wallis, ANOVA, and post hoc Tukey tests. The results showed that 55.6% of oncology patients and 32.2% of healthcare workers had used CAM at least once. Oncology patients were more likely to use CAM than healthcare professionals, and among healthcare professionals, nurses/technicians used CAM more frequently than physicians. Significant differences in attitudes were observed based on sociodemographic factors. Positive attitudes were more common among women, older adults, individuals with lower education levels, nurses/technicians, those with longer work experience, non-oncology healthcare workers, believers, and those with lower incomes. Marital status and place of residence showed no significant effect. This study highlights a gap between cancer patients’ frequent, unsupervised CAM use and healthcare providers’ often skeptical attitudes, particularly among physicians. The findings underscore the need for targeted education for healthcare professionals, development of CAM management guidelines in oncology, and fostering open dialogue between patients and providers to optimize outcomes. Longitudinal research is recommended to explore CAM’s impact on clinical outcomes.